(untitled) (Eurasian Journal of Ecology, 2026)
The presented work defines the species composition of the algal flora within the saline region of Lake Balkhash and involves isolating novel and promising cultures of microalgae and cyanobacteria, followed by examining their morphological, cultural, and physiological traits. The taken results indicated that the algal flora in water samples from the eastern coast of Balkhash is composed of diatoms (Bacillariophyta) at 40.33%, green algae (Chlorophyta) at 32%, cyanobacteria (Cyanophyta) at 19.33%, and euglenoids (Euglenophyta) at 8.33%. The specimens were classified into 4 divisions, 6 classes, 6 orders, 11 families, and 22 genera. Through the application of microbiological techniques, eight axenic pure cultures of microalgae and cyanobacteria were successfully isolated and determined, including Oscillatoria sp, Nostoc sp, Arthrospira sp., Anabaena sp, Chlorella vulgaris, Parachlorella kessleri, Dunaliella salina, and Navicula sp. Optimal cultivation conditions were determined for each strain. The isolated cyanobacterial cultures exhibited the highest growth rate on BG-11 and Zarrouk nutrient media at pH 7–9 and an optimal temperature of 28–32 °C. The isolated microalgae cultures showed effective growth on Tamia, Artaria, and BG-11 nutrient media at pH 6.5–7.5 and a temperature of 27–30 °C.The obtained pure cultures are notably valuable in industrial biotechnology, particularly for the development of biologically active supplements. Keywords: algae, isolation of axenic pure cultures, microalgae and cyanobacteria cultures, saline lake.